Network toxicology and molecular docking to investigate the mechanism of bisphenol A toxicity in human diabetic cardiomyopathy - Bo Li; Xu Zhao; Yan Ding; Yi Zhang (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA), a ubiquitous endocrine-disrupting chemical, is widely used in polymers, plasticizers, and food packaging, raising significant concerns for human health. Growing evidence links BPA exposure to cardiovascular diseases, including diabetic cardiomyopathy (DCM), a severe complication of diabetes characterized by myocardial dysfunction. This study employs an integrative approach combining network toxicology and molecular docking to elucidate the molecular mechanisms underlying BPA-induced DCM. Using computational tools such as ADMETlab2.0, ProTox3.0, GeneCards, OMIM, Swiss Target Prediction, and ChEMBL databases, we systematically predicted BPA's potential to induce DCM and constructed comprehensive disease and BPA target libraries. Venn diagram analysis identified 93 potential targets associated with BPA-induced DCM, and a robust BPA regulatory network was established using Cytoscape. Functional enrichment analyses revealed significant involvement of oxidative stress, insulin signaling, and metabolic pathways in BPA toxicity. Molecular docking simulations demonstrated stable binding interactions between BPA and core targets (INS, AKT1, PPARG, STAT3, PPARA, MMP9), with binding energies ranging from −5.3 to −7.5 kcal/mol. Our findings indicate that BPA may induce DCM through key genes and pathways, including cGMP−PKG signaling pathway, insulin signaling pathway, AMPK signaling pathway, and HIF−1 signaling pathway. This study provides a novel theoretical framework for understanding the molecular pathogenesis of BPA-induced DCM and highlights the potential of network toxicology in identifying toxic pathways for uncharacterized environmental compounds. These insights offer potential targets for preventive and therapeutic strategies against BPA-associated cardiovascular complications.